2006
DOI: 10.1051/0004-6361:20066098
|View full text |Cite
|
Sign up to set email alerts
|

The hot subdwarf B + white dwarf binary KPD 1930+2752

Abstract: Context. The nature of the progenitors of type Ia supernovae is still under debate. KPD 1930+2752 is one of the best SN Ia progenitor candidates known today. The object is a double degenerate system consisting of a subluminous B star (sdB) and a massive white dwarf (WD). Maxted et al. (2000) conclude that the system mass exceeds the Chandrasekhar mass. This conclusion, however, rests on the assumption that the sdB mass is 0.5 M . However, recent binary population synthesis calculations suggest that the mass of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
181
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 135 publications
(192 citation statements)
references
References 43 publications
11
181
0
Order By: Relevance
“…The synthetic spectra are convolved at a resolution of 1.0 Å. a practical recipe for computing some sort of saturated metallicity in model atmospheres, namely multipling the solar abundances of metals by a factor 10, for example. This is the same as the suggestion previously made by O'Toole & Heber (2006), Geier et al (2007), and Gianninas et al (2010), but with the added justification of the saturation effect. Figure 3 furthermore reveals that the saturation effect is verified over the full range of parameters displayed in the plot.…”
Section: Exploring Metallicity Effects On Spectral Linessupporting
confidence: 82%
“…The synthetic spectra are convolved at a resolution of 1.0 Å. a practical recipe for computing some sort of saturated metallicity in model atmospheres, namely multipling the solar abundances of metals by a factor 10, for example. This is the same as the suggestion previously made by O'Toole & Heber (2006), Geier et al (2007), and Gianninas et al (2010), but with the added justification of the saturation effect. Figure 3 furthermore reveals that the saturation effect is verified over the full range of parameters displayed in the plot.…”
Section: Exploring Metallicity Effects On Spectral Linessupporting
confidence: 82%
“…Spectral lines of hydrogen and helium were fitted by means of chi-squared minimization using SPAS, and statistical errors were calculated with a bootstrapping algorithm. Minimum errors reflecting systematic shifts when using different model grids (ΔT eff = 500 K; Δ log g = 0.05; Δ log y = 0.1, for a discussion see Geier et al 2007) have been adopted in cases where the statistical errors were lower. Example fits for a typical sdB, an sdOB and a He-sdO star are shown in Fig.…”
Section: Final Target Samplementioning
confidence: 99%
“…Transfer of mass or the subsequent merger of the system may cause the WD to approach the Chandrasekhar limit, ignite carbon under degenerate conditions, and explode as a SN Ia (Webbink 1984;Iben & Tutukov 1984). One of the best-known candidate systems for this double degenerate merger scenario is the sdB+WD binary KPD 1930+2752 (Maxted et al 2000a;Geier et al 2007). Mereghetti et al (2009) showed that in the X-ray binary HD 49798 a massive (>1.2 M ) white dwarf accretes matter from a closely orbiting subdwarf O companion.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case for the sdB+WD binary KPD 1930+2752, which is the best known DD progenitor candidate for SN Ia (Maxted et al 2000;Geier et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of the sdB+WD binary KPD 1930+2752, however, has highlighted the importance of such systems as SN Ia progenitor candidates (Billères et al 2000;Maxted et al 2000;Geier et al 2007). Hot subdwarf stars (sdBs) are core helium-burning stars situated at the hot end of the horizontal branch with masses around 0.5 M (Heber 1986).…”
Section: Introductionmentioning
confidence: 99%